2018
DOI: 10.3390/app8112161
|View full text |Cite
|
Sign up to set email alerts
|

Low Noise High-Energy Dissipative Soliton Erbium Fiber Laser for Fiber Optical Parametric Oscillator Pumping

Abstract: We report on a mode-locked erbium-doped fiber laser delivering highly-chirped pulses with several tens of nanojoules of energy around 1560 nm and its exploitation to efficiently pump a fiber optical parametric oscillator (FOPO), thus enabling picosecond pulse generation around 1700 nm. The laser cavity features a high normal dispersion and mode-locking is sustained using tailored spectral filtering combined with nonlinear polarization evolution and a semiconductor saturable absorber. Numerical simulations show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…After numerical simulations, they found that the best results could be obtained using a 7-meter-long DSF. By optimizing the pump wavelength and the temporal dispersion tuning of the FOPO, they obtained a picosecond pulsed laser output with tunable wavelengths from 1617-1876 nm, and the pulse energies with the average power of 14.3 mW at the wavelength of 1668 nm for a pump wavelength of ~1566nm, as shown in the Fig 13 . Later, they used the same experimental setup and increased the width of intra-cavity filter in pump source to optimize the parameter of chirped pulse (reached to 13 nJ, 35 ps) [49], achieving the picosecond ultrashort pulse with the average power of 204 mW. Figure 13.…”
Section: Fwm-based Implementation Methodsmentioning
confidence: 99%
“…After numerical simulations, they found that the best results could be obtained using a 7-meter-long DSF. By optimizing the pump wavelength and the temporal dispersion tuning of the FOPO, they obtained a picosecond pulsed laser output with tunable wavelengths from 1617-1876 nm, and the pulse energies with the average power of 14.3 mW at the wavelength of 1668 nm for a pump wavelength of ~1566nm, as shown in the Fig 13 . Later, they used the same experimental setup and increased the width of intra-cavity filter in pump source to optimize the parameter of chirped pulse (reached to 13 nJ, 35 ps) [49], achieving the picosecond ultrashort pulse with the average power of 204 mW. Figure 13.…”
Section: Fwm-based Implementation Methodsmentioning
confidence: 99%
“…One is based on population inversion to generate 1.7 µm pulsed lasers by using rare-earth-doped fibers, such as thulium-doped fibers [6,7,10,11], thuliumholmium-codoped fibers [12,13], and bismuth-doped fibers [14][15][16]. The other is based on nonlinear effects in solid-core fibers to realize a frequency conversion, such as soliton self-frequency shift [17][18][19][20], four-wave mixing [21][22][23], self-phase modulation [7,24,25], and stimulated Raman scattering (SRS) [26]. Recently, fiber gas Raman lasers (FGRLs) based on hollow-core photonic crystal fibers (HC-PCFs) have opened a new opportunity for 1.7 µm pulsed fiber lasers [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting the studies of quantum effects for dissipative solitons in the optical parametric oscillator [10]. For practically important temporal solitons in driven microresonators, the main noise sources are currently technical and thermal [11,12]. However, the limiting application possibilities of the solitons are determined precisely by quantum fluctuations.…”
Section: Introductionmentioning
confidence: 99%